Minimasi Biaya Distribusi Es Balok Dan Es Kristal Menggunakan Metode Capacitated Vehicle Routing Problem Di PT Agronesia Es Saripetojo Bandung - Agus Purnomo; Hariadi Ismail; Ramadhan Surya Dinata (Universitas Logistik dan Bisnis Internasional, 2023)
Companies can minimize distribution costs by determining the best distribution route from the company (depot) to customers spread across various locations. PT Agronesia Es Saripetojo Bandung Division has a problem determining the best distribution route because the distribution route changes every day depending on the customer's communication with the driver who asks to be served first. Thus the company cannot measure the performance of distribution costs and cannot evaluate the optimal number of vehicles to support distribution cost efficiency. This problem can be solved using the Capacitated Vehicle Routing Problem (CVRP) method which takes into account the number and capacity of vehicles, the demand for each replacement, and the distance from the depot to the customer so that a minimum total distribution cost is obtained. The results of the research provide a solution for the distribution of ice blocks and crystal ice using the Capacitated Vehicle Routing Problem (CVRP) method with the help of LOGWARE software, it has succeeded in determining the best route and at the same time minimizing distribution costs. Distribution cost efficiency can still be done by reducing 1 Mitsubishi Colt Diesel Engkel FE 71 vehicle, so there is an efficiency of = Rp. 267,000,-/day = 8.04%/day. Meanwhile, by reducing 1 Colt Diesel Engkel FE 71 vehicle, an efficiency of = Rp. 267,000,-/day = 7.92%/day. Meanwhile, vehicles that are not used can be rented or sold, thereby reducing the burden of fixed costs and variable costs.